Gill asymmetry in Labeo ogunensis from Ogun river, Southwest Nigeria - Ayoade, A A (Universidad de Costa Rica, 2004)
Fluctuating asymmetry (FA), often used as indicator of environmental stress, was evaluated in gill rakers and filaments of Labeo ogunensis from Ogun river, Southwest Nigeria. Mean length and weight of 13.68+1.28 cm and 59.40+17.48 g were respectively recorded. The gill rakers (t = -0.919) and filaments (t = -1.150) from both sides were not significantly different. The gill filaments recorded (0.31+2.42) higher incidence of fluctuating asymmetry (FA) compared with the gill rakers (0.21+1.58), signifying developmental interference in the population. Fish size and sex were observed to exert minimal influence on FA.